Critical level and distribution of phosphorus in common bean cultivated in different soils under cerrado vegetation - de Carvalho, Arminda Moreira; Fagéria, Nand Kumar; Kinjo, Toshiaki; de Oliveira, Itamar pereira (Pesquisa Agropecuaria Brasileira, 1993)
In a greenhouse experiment the effect of P levels (0, 25, 50, 100, 200 and 400 mg P.kg-1) in soils of cerrado (Dark-Red Latosol, Duskey Red Latosol, Red-yellow Latosol, and Quatzipsament on the distribution and critical P levels in plant bean (Phaseolus vulgaris L.) was studied. Phosphorus levels influenced significantly the concentration and accumulation of P in the plant tops, except in AQd at 90 days of growth. Critical P levels in the tops of the plants were 0,20% in LRd and 0,28% in AQd. In relation to P distribution in the plant, approximately 15% of P accumulated remained in the tops and the rest was translocated to grains in LRd and LEd. The plant tillage in the LVd and AQd soils showed an average 10% of P accumulated in the tops and 90% in the grains.